The precarious state of the hydrosphere: why biocultural health matters. (11th November 2013) - Johnston, Barbara Rose; Fiske, Shirley J.
<x xml:space="preserve">Abstract</x> While the fundamental role of water as a human need and a human right has been acknowledged by the United Nations and member states, too often strategies to secure that right conflict with the competing interests and actions for the same resource. We are approaching a global tipping point in the hydrosphere where the biocultural sustainability of water resources is threatened by the cumulative and synergistic impacts of degenerative changes. When water that sustains life, livelihoods, and culture is threatened, the cultural stability and diversity of peoples and their environment is also threatened. Achieving long‐term sustainability of our hydrosphere requires re‐embedding social, cultural, and environmental concerns within and throughout the local, regional, and global systems that plan, finance, develop, manage, and use our world's water. WIREs Water 2014, 1:1–9. doi: 10.1002/wat2.1003 Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.